Biologic and Abiotic Factors Regulate Dissolved Organic Nitrogen With Low and High Nutrient Concentrations on Tibetan Plateau, Respectively - Li, Shaoyu; Sun, Jian; Zhou, Tiancai; Zhao, Mengli; Cong, Nan; Zhang, Lin (Frontiers in Environmental Science, 2021)
Although dissolved organic nitrogen (DON) plays an important role in the dynamic processes of nitrogen mineralization, fixation and leaching, the ecological driving forces of DON across the Tibetan Plateau remain largely unknown. Here, we measured climate, soil, plant indicators and DON concentration on the Tibet Plateau, and used “Change-point” analysis to determine DON patterns. Then correlation analysis was applied to analyze the relationship between DON and each index. Finally, the structural equation model (SEM) is used to explain the overall effect between DON and environmental factors. Our results showed that two DON patterns were presented across the Tibetan Plateau, i.e., low-DON (5.43 g/mg) and high-DON (16.36 g/mg) patterns. In the Low-DON pattern, biologic factors such as microbial carbon, microbial nitrogen and productivity were the main influencing factors of DON concentration. In the high-DON pattern, DON was strongly governed by hydrothermal synchronization and superior soil environment. This study can help for us to have a more comprehensive understanding of the response mechanism of soil soluble nitrogen pool in alpine ecosystems under climate change.